Do birth outcomes mediate the association between drug use in pregnancy and neonatal metabolic bone disease? A prospective cohort study of 10,801 Chinese women - Jiang, Honglin; Guo, Jialin; Li, Jing; Li, Chunlin; Du, Wenchong; Canavese, Federico; Xie, Feng; Li, Huajing; Yang, Jian; Ying, Hao; Hua, Jing (Frontiers in Public Health, 2024)
Background: Prenatal drug use can cause toxicity in bone health in newborns. We aimed to examine whether birth outcomes mediate the association between medication use and neonatal metabolic bone disease (MBD).A prospective cohort of 10,801 pregnant women (17-49 years) and their infants followed at a single center from 1 st January, 2012 to 31 st December, 2021 were included. Based on four single drugs, comprehensive medication use was determined and categorized into three groups using latent class analysis: Group 1 included antibiotics and Furosemide or fewer than two drugs except MgSO4, Group 2 included MgSO4 without antibiotics or Furosemide, and Group 3 encompassed Dexamethasone and antibiotics. Mediation analysis was conducted to assess the mediating effects of prematurity, low birth weight (LBW) and small for gestational age (SGA).Results: There were 138 (1.3%) infants with MBD; 2701 (25%) were born preterm, 1717 (15.9%) had LBW, and 303 (2.8%) were SGA. Pregnant women in Groups 2 and 3 had 2.52 to 14.66 times higher risks of delivering an infant with MBD compared to Group 1. Only LBW showed a significant mediating effect on the association between comprehensive medication use and MBD, with a mediation proportion of 51.8% (45.0%–64.1%, P < 0.001). Conclusions: Comprehensive medication use during pregnancy was associated with an increased risk of neonatal MBD, largely mediated by LBW. Early antepartum monitoring and prevention targeting adverse birth outcomes are necessary to mitigate the risk of MBD.